Analisis Pengaruh Persepsi dan Pendidikan Terhadap Niat Individu Berwakaf Uangan Dengan Kesadaran Relius Sebagai Variabel Intervening - Amrizal; Muhammad Syahrum Alfan; Yayat Sujatna; Yeni Oktaviani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to analyze the influence of perception and education on individuals' intentions to donate cash, with religious awareness as an intervening variable. This research design uses exploratory quantitative with a sample size of 100. Collective data uses a questionnaire with a Linkert scale. This research was conducted in Tangerang City using quantitative methods and Structural Equation Modeling (SEM) analysis via SmartPLS. The research results show that perception has no significant effect on intention to give waqf, while education has a positive and significant effect on intention to give waqf. Religious awareness does not function as a mediator between perception and education on the intention to give waqf. These findings provide important insights for the development of education and outreach programs regarding cash waqf in society.